2012
DOI: 10.2134/agronj2011.0264
|View full text |Cite
|
Sign up to set email alerts
|

Economizing Nitrogen Fertilizer in Wheat through Combinations with Organic Manures in Kashmir, Pakistan

Abstract: indicated that the grain yield of wheat in all the treatments involving organic amendments, that is, composted FYM, vermicompost, and lantana compost was markedly lower (36-65% and 23-54% in the 2 yr) than with the mineral fertilizer treatment. However, application of these organic amendments improved soil properties in terms of lower bulk density; increased pH, oxidizable organic C, total N, available P and K in the soil; and increased the P, K, and protein contents of seed compared with mineral N. ABSTRACT I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…The SOM was determined by oxidizing SOM in the soil samples with K2Cr2O7 in concentrated sulfuric acid for 30 min followed by titration of the excess K2Cr2O7 with ferrousammonium sulfate [16]. The Kjeldahl method was used for soil total N determination, the Olsen extraction method was used for available P estimation [17], and the available K was determined by a flame photometer [18].…”
Section: Sampling and Sample Analysismentioning
confidence: 99%
“…The SOM was determined by oxidizing SOM in the soil samples with K2Cr2O7 in concentrated sulfuric acid for 30 min followed by titration of the excess K2Cr2O7 with ferrousammonium sulfate [16]. The Kjeldahl method was used for soil total N determination, the Olsen extraction method was used for available P estimation [17], and the available K was determined by a flame photometer [18].…”
Section: Sampling and Sample Analysismentioning
confidence: 99%
“…Seed samples were dried at 65°C for about 48 h, ground to pass through a 1‐mm sieve, and then analyzed for N, P, and K concentrations using the procedures described for plant analysis. The NPK uptake was calculated from the DMY and NPK concentration in the respective plant parts (Fernandez et al, 2008; Abbasi and Tahir, 2012). Total NPK uptake was the sum of straw and seed NPK uptake.…”
Section: Methodsmentioning
confidence: 99%
“…The N contents and N uptake in both the seed and straw of soybean were used for calculating the different N efficiency parameters, i.e., the agronomic efficiency of applied N (NAE), the physiological efficiency of applied N (NPE), and the N use efficiency (NUE), by the methods described by Nyiraneza and Snapp (2007) and reported by Abbasi and Tahir (2012). To consider N from N 2 fixation, the fixed N (kg ha −1 ) was subtracted from the total plant N (total plant N uptake), and the NAE, NPE, and NUE calculations were made with the remainder.…”
Section: Methodsmentioning
confidence: 99%
“…The application of poultry manure alone or in combination with wheat straw residues and urea gave a significant increase in pH, while urea N and wheat straw residues tended to decline pH showing acidifying effect on soil (Abdul et al, 2014). Previous studies showed that the application of poultry manure and farmyard manure increased soil pH (Abbasi, & Tahir, 2012). The higher pH in poultry manure amended soil is probably due to the release of OH − ions during decomposition of manure and the buffering from organic compounds released from manure ( Zingore et al, 2008;Azeez et al, 2010).…”
Section: Land Use Change Effects On Chemical Soil Propertiesmentioning
confidence: 96%
“…The decrease in the BD might be related to the accumulation of higher organic matter from the added organic amendments. Soils amended with organic or inorganic amendments showed a reduction in BD (Abbasi & Tahir, 2012;Abbasi et al, 2010;Bandyopadhyay et al, 2010). The decrease in BD was due to the higher organic matter content, better soil aggregate, better least limiting water range and increased root growth with lower cone penetration resistance and bio pores due to high organic matter content (Bandyopadhyay et al, 2010).…”
Section: Land Use Change Effects On Physical Properties Of Soilmentioning
confidence: 99%